2022
DOI: 10.3390/ijerph19127321
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Household Waste Segregation Behaviour in Urban Community in Ujjain, India: A Framework Analysis

Abstract: Waste segregation practices must be socially acceptable, affordable, context-specific, and participatory, which is essential for promoting waste segregation. Therefore, this study explored the urban community members’ motivation, opportunity, and household waste segregation ability. We performed a qualitative study in Ujjain city, India. Ten focus group discussions and eight in-depth interviews were conducted with female and male household members in residential and slum areas. All interviews were digitally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…The reason for this was the education of community members and even children in schools. The results of this study showed that women do more waste separation than men [ 22 ]. The study by Cheng et al showed that knowledge has a positive effect on waste separation behaviour and that women participate more in waste separation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason for this was the education of community members and even children in schools. The results of this study showed that women do more waste separation than men [ 22 ]. The study by Cheng et al showed that knowledge has a positive effect on waste separation behaviour and that women participate more in waste separation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Mugambe et al, community support was a decisive factor for waste separation behaviour [ 37 ]. A qualitative study from India showed that subjective norms are the strongest predictors of waste separation behaviour [ 22 ]. The results of a study have shown that social capital has a positive effect on waste separation behaviour [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TPB posits that the generation of environmental behavior comes from an individual’s own expectations and welfare, proposing that behavioral attitudes (BAs), subjective norms (SNs), and perceived behavioral control jointly determine an individual’s environmental behavior [ 7 ]. Currently, The TPB has consistently demonstrated its utility and efficacy in explaining recycling in European countries and domestic waste classification in various settings and contexts, including LMICs in the Eastern Mediterranean (Turkey and Greece), Africa (South Africa and Ghana), and Asia (India, Iran, Saudi Arabia, and China) [ 9 , 10 , 11 ]. Therefore, introducing the TPB into FDW classification management behavior research, from the aspects of rural residents itself, to explore the internal factors influencing the desire and behavior of its classification can improve the enthusiasm for FDW classification management.…”
Section: Introductionmentioning
confidence: 99%